Boundary clauses and the use of the vernacular in eastern Frankish charters, c.750–c.9001. Issue 254 (22nd October 2018) - Roberts, Edward
Abstract: Of the thousands of surviving charters from eastern Carolingian Francia, remarkably few contain boundary clauses, even though ceremonial perambulations were a prominent aspect of property transactions. This article examines these boundary clauses asking when and why perambulations were written down in charters, and why, in an overwhelmingly Latin charter tradition, this was often done with vernacular language. The analysis suggests that boundary clauses were intended as rhetorical statements of elite identification and authority, usually signalling the involvement of powerful patrons and significant properties. The article contributes to debates concerning ritual, rhetoric and the interaction between orality and literacy in medieval charters.